Jamming against GNSS receivers: attacks and mitigation techniques - Lisi, Marco (GEOmedia, 2023)
Jamming interference to GNSS receivers is a growing threat as more systems and devices rely on GNSS for Positioning, Navigation, and timing (PNT). The European GNSS Agency (GSA today EAASA) estimated there were 6.4 billion GNSS-enabled devices in use worldwide in 2019, and forecasts this will rise to 9.5 billion by 2029 — equivalent to 1.1 devices for every person in the world.